MEASURING THE PERFORMANCE OF ISLAMIC BANKING IN INDONESIA: AN APPLICATION OF MASLAHAH-EFFICIENCY QUADRANT (MEQ) - Rusydiana, Aam Slamet; Sanrego, Yulizar Djamaluddin (Journal of Islamic Monetary Economics and Finance, 2018)
Despite of market condition under perfect or unperfect competition, Islamic banking has to reach their level of efficiency in order to succeed and make a profit; those who do not will fail and be forced to exit the market. However apart of having a sound performance, Islamic banking also has to comply with the sharia principles. This paper aims to have efficiency and maslahah measurement in one assessment framework that is maslahah-efficiency quadrant (MEQ). The study from 2011-2014 revealed that Bank Muamalat Indonesia (BMI) and Sharia Panin Bank are excellent since both are within the first quadrant. Whereas Bank Sharia Mandiri (BSM), Sharia Maybank, and Sharia Bukopin Bank are considered good at the second quadrant; Bank Rakyak Indonesia Sharia (BRI) and BCA Sharia are fair at the third; and Bank Mega Sharia, Victoria Sharia, Bank Negara Indonesia Sharia (BNI), and Bank Jabar Banten Sharia (BJB) are poor at the fourth sequentially. It is urge for Islamic bank that are in low level of MSI to have a critical policy to keep in line with the five factor of maqashid sharia apart of having efficiency in order to reach maslahah.